Implementasi Metode Fuzzy TOPSIS untuk Seleksi Penerimaan Karyawan - Sri Lestari; Widodo Priyodiprodjo (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2011)
Abstract —An emerging institution would continue to need qualified workers to produce good performances.  Seeing the importance of high quality employees, the candidate selection process became an important part and should be performed promptly.  It is also important to have candidates with desirable criteria fit to the institution. Many proposed methods can be adapted to help employee selection process based on criteria.  This research propose an employee selection system based on Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, because the proposed method capable to deal with multi dimensional problems in employees selection.  The system will produce ranks that can be used to help the hiring decision. This research also compares the results from TOPSIS method and WPM method.  The comparison result shows that both methods produce the same ranks for the chosen candidates.Keywords—  Fuzzy TOPSIS, WPM, Employee Selection.